Efikasi Diri Sebagai Prediktor Kebahagiaan Pada Usia Dewasa Muda - Maria Delciello Romasari Simbolon; Wustari L. Mangundjaya (Madani: Jurnal Ilmiah Multidisiplin, 2023)
The variety of developmental tasks in young adults is often a contributing factor to weaken levels of happiness. Low levels of happiness in individuals can lead to pessimism, low self-esteem, difficulty being in a social environment, and low self-confidence. Lack of self-confidence is the impact of a person's low self-efficacy. This study aims to examine the effect of self-efficacy on happiness in young adults. The research design used a quantitative research method with a convenience sampling approach with a simple linear regression technique used to analyze data from this study, using SPSS version 25, with respondents as many as 104 young adults as psychology students. The results of the regression test show that auto-efficiency affects happiness by 0.260 with a positive significance of 0.000.Â  Based on the results of the regression equation, had been found that the constant value was 13.974, which means that without self-efficacy, student happiness is only 13.97%. Thus, it can be said that self-efficacy has a positive and significant effect on the happiness of students of the Faculty of Psychology, University "X" students.